Ecological risk assessment of metals in small craft harbour sediments in Nova Scotia, Canada. (September 2019) - Zhang, Hongling; Walker, Tony R.; Davis, Emily; Ma, Guofeng
Abstract: Ecological risk assessment of metals (As, Cd, Cr, Cu, Hg, Ni, Pb and Zn) in surface sediments from 31 small craft harbours (SCHs) in Nova Scotia, Canada was conducted using multiple risk assessment approaches. Approaches used were contamination factor, pollution load index, geoaccumulation index, potential ecological risk factor for individual metals, comprehensive potential ecological risk index, mean probable effect level quotient and mean effects range median quotient. Results indicated most SCHs exhibited low ecological risk from sediment metal concentrations, except for two harbours. Metal contamination was highest in Canso Harbour, followed by Clarks Harbour. SCH sediments were only slightly contaminated with low probability of pollution according to mean probable effect level and mean effects range median quotients. However, pollution load and geoaccumulation indexes indicated Cd and Hg had the highest metal contamination across SCH sediments. Cadmium and Hg had the highest potential ecological risk, respectively compared to other metals. Graphical abstract: Unlabelled Image Highlights: Risk assessment of metals in small craft harbour (SCH) sediments was conducted. Multiple ecological risk assessment approaches were assessed in 31 SCHs in Nova Scotia. SCHs sediments had 9–10% probability of toxicity and categorized as slightly toxic. Potential ecological risk of Cd was higher than other metals. Canso and Clarks Harbour exhibited highest ecological risk compared to other SCHs.